Pembentukan Pendidikan Karakter Siswa Melalui Kegiatan Ekstrakurikuler Pramuka di Madrasah Aliyah Nurul Amin Kubu Padi Kalimantan Barat - Nasiruddin (STAI Ma'had Aly Al-Hikam Malang, 2024)
This article aims to describe the formation of character education for students through scout extracurricular activities at MAS Nurul Amin Kubu Padi, Kuala Mandor B District, Kab. stronghold. Explain the supporting and inhibiting factors in the formation of student character education through scout extracurricular activities at MAS Nurul Amin Kubu Padi, West Kalimantan.This study used descriptive qualitative method. This research aims to describe social phenomena as they are based on the data presented and the results of the discussion presented above, it can be concluded that the formation of students' disciplined character consists of five elements, namely structure and discipline, basic skills training, independence and responsibility, experience in the open air and teamwork in extracurricular activities. Scouts have a large role in strengthening students' disciplinary character. Through it all, students learn to respect time, follow procedures, and behave in an orderly manner. Developing disciplined character through Scouting can make a positive contribution to the formation of students who have high discipline.